Improving MiniHip femoral prosthesis positioning using a cross‐laser projection system in total hip arthroplasty by an anterolateral supine approach. Issue 2 (9th January 2021) - Fujii, Hideki; Hayama, Tetsuo; Abe, Toshiomi; Takahashi, Motoi; Matsushita, Yohei; Sato, Ryuichi; Otani, Takuya; Saito, Mitsuru
Abstract: Background: The authors developed a cross‐laser projection system (CLP) to place a femoral neck‐sparing short stem using the minimally invasive anterolateral supine approach in total hip arthroplasty. This study aimed to verify the utility of CLP. Methods: Thirty joints were assessed with the MiniHip (Corin). The authors compared femoral component implantation with a patient‐specific femoral osteotomy guide (PSG) for the femoral neck‐cut (PSG group), with the CLP attached to the rasp handle to irradiate the cross‐laser to the target of PSG (CLP group), and without PSG or CLP (control group). Results: In the CLP group, the positional deviation of anteversion, anterior/posterior tilt and varus/valgus placement of the stem postoperatively were 1.8° ± 0.2°, 2.0° ± 2.0° and 2.0° ± 0.1°, respectively. The positional deviation of anteversion ( p  < 0.001) and anterior/posterior tilt ( p  = 0.036) were significantly smaller than those in the other groups. Conclusions: CLP improves the accuracy of MiniHip femoral prosthesis placement.